2016
DOI: 10.1186/s40101-016-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating CD34-positive cells and serum alkaline phosphatase in relation to body mass index for elderly Japanese men

Abstract: BackgroundRecent studies have confirmed an association between bone metabolism and vascular homeostasis. However, no study has examined the relationship between serum alkaline phosphatase (ALP) (a marker of bone metabolism) and circulating immature cell such as CD34-positive cells (a marker of vascular homeostasis).MethodsWe conducted a cross-sectional study of this association in 272 elderly Japanese men (60–79 years). Because low body mass index (BMI) status is a known characteristic of Japanese with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A reduction in CD34-positive cells has been approved to be related to increased infarction numbers (35). Studies have reported that ALP level was positively related to the number of CD34-positive cells, therefore we speculated that low ALP level may lead to an increased likelihood of poor outcomes by affecting the number of CD34-positive cells (35,36). Our results suggest that either higher or lower ALP levels are related to mortality and recurrence after stroke, providing new insight into the underlying mechanisms of the ALP impact on stroke outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…A reduction in CD34-positive cells has been approved to be related to increased infarction numbers (35). Studies have reported that ALP level was positively related to the number of CD34-positive cells, therefore we speculated that low ALP level may lead to an increased likelihood of poor outcomes by affecting the number of CD34-positive cells (35,36). Our results suggest that either higher or lower ALP levels are related to mortality and recurrence after stroke, providing new insight into the underlying mechanisms of the ALP impact on stroke outcomes.…”
Section: Discussionmentioning
confidence: 92%